Priprava programov razkuževanja za preprečevanje infekcij v zdravstveni dejavnosti - Skubic, Milena (Obzornik zdravstvene nege, 1999)
The article stresses the need for the formation of prevention programs for infections in health services. In the frames of programs for the prevention ofinfections, the author describes desinfection. The need for the formation ofprevention programs is founded in the directives from the Act on infectious diseases. The advanatges of prevention programs are a unified doctrine for desinfection, quality performance, better surveillance and supression of infections and lower expensed. The article presents a basic model of a programof desinfection in a health institution.
Keywords: Cross infection; dezinfekcija; Disinfection; Health services; Hygiene; infekcije; nadzor; preprečevanje; Prevention and control; zdravstvene ustanove